2017
DOI: 10.15406/jlrdt.2017.03.00063
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Liver Dysfunction in Patients with Dengue Infection and the Markers of Severe Disease: Study from a Tertiary Care Centre in Punjab

Abstract: Introduction: Dengue is a major international health concern that is prevalent in tropical and sub tropical countries. Study of dengue infection and its Liver complications are scarce from countries like India. This study was done to assess the frequency and spectrum of liver dysfunction in Dengue infection patients. Patients and Methods:A hospital based record analysis study was performed at a tertiary care centre. All the inpatients (>18 years) who were diagnosed with dengue infection between January 2015 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…This preferential elevation of AST over ALT was also noted in our study. Similarly, studies by de Souza LJ et al [22] , Chhina RS et al [20] and Soni A et al [12] also showed a greater elevation in AST than ALT levels.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This preferential elevation of AST over ALT was also noted in our study. Similarly, studies by de Souza LJ et al [22] , Chhina RS et al [20] and Soni A et al [12] also showed a greater elevation in AST than ALT levels.…”
Section: Discussionmentioning
confidence: 59%
“…Liver damage has been found to be more common among females in the large study from Brazil by de Souza LJ et al (74.6% of females vs 52.2% of males) [9] . However, studies by Soni A et al [12] and Bagepally RS et al [15] showed male preponderance (M:F ratio 2:1 and 2.5:1 respectively). Our study also showed slight overall male preponderance (M:F ratio 1.1:1) while the male to female ratio in patients with hepatic dysfunction was 2.8:1.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…DF initiates the inflammatory responses leading to liver parenchymal changes and causing release of transaminases in circulation [7,10] . In approximately 90% of the patients with DF, Aspartate Aminotransferase (AST) is higher than the Alanine Aminotransferase (ALT) [5,11] . We studied 100 patients with dengue that were admitted to Khaja Bandanawaz teaching and general hospital.…”
Section: Discussionmentioning
confidence: 99%
“…WHO 2018 report increase in number of cases from 2.2 million in 2010 to 3.2 million in 2015 [1] . Dengue virus was isolated in India for the first time in 1945 and poor hygiene and weaker health system are the factors for spread of the disease [5] . After an incubation period of 4-8 days, classical dengue fever presents as fever, generalized body ache, myalgia, arthralgia, and headache [6] .…”
Section: Introductionmentioning
confidence: 99%